EphrinA1-targeted nanoshells for photothermal ablation of prostate cancer cells - Andre M Gobin; James J Moon; Jennifer L West (International Journal of Nanomedicine, 2008)
Andre M Gobin, James J Moon, Jennifer L WestDepartment of Bioengineering, Rice University, Houston, TX, USAAbstract: Gold-coated silica nanoshells are a class of nanoparticles that can be designed to possess strong absorption of light in the near infrared (NIR) wavelength region. When injected intravenously, these nanoshells have been shown to accumulate in tumors and subsequently mediate photothermal treatment, leading to tumor regression. In this work, we sought to improve their specificity by targeting them to prostate tumor cells. We report selective targeting of PC-3 cells with nanoshells conjugated to ephrinA1, a ligand for EphA2 receptor that is overexpressed on PC-3 cells. We demonstrate selective photo-thermal destruction of these cells upon application of the NIR laser.Keywords: nanoshell, near infrared, photothermal treatment, prostate cancer